1958
DOI: 10.1113/jphysiol.1958.sp006003
|View full text |Cite
|
Sign up to set email alerts
|

The electrical activity of the bundle of His

Abstract: The initial purpose of the present study was to find an explanation for the long time interval elapsing between the activation of the auricle and the ventricle. Considering the fact that the auriculo-ventricular (A.V.) node is a structure which the impulse coming from the auricle traverses on its way towards the ventricle, it seemed likely that an explanation for the A.V. latency could be found by studying its activity. It was also expected that the node should reveal its activity through an action potential w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
5

Year Published

1959
1959
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(38 citation statements)
references
References 1 publication
1
32
0
5
Order By: Relevance
“…The electrical activity recorded from the His bundle appeared as a rapid biphasic or triphasic deflection occurring at the same point of the P-R interval (± 3.0 msec) in several successive cardiac cycles. Furthermore, the configuration and temporal relationships of these deflections are the same as that obtained in experimental studies in which placement of recording electrodes on the His bundle was performed by direct visualization during cardiotomy.2 9 Although the amplitude of the deflection varied slightly throughout the recording period, the general configuration did not change. The amplitude variation was probably due to the slight catheter movement resulting from cardiac contraction.…”
Section: Methodsmentioning
confidence: 48%
“…The electrical activity recorded from the His bundle appeared as a rapid biphasic or triphasic deflection occurring at the same point of the P-R interval (± 3.0 msec) in several successive cardiac cycles. Furthermore, the configuration and temporal relationships of these deflections are the same as that obtained in experimental studies in which placement of recording electrodes on the His bundle was performed by direct visualization during cardiotomy.2 9 Although the amplitude of the deflection varied slightly throughout the recording period, the general configuration did not change. The amplitude variation was probably due to the slight catheter movement resulting from cardiac contraction.…”
Section: Methodsmentioning
confidence: 48%
“…Given a diameter of Purkinje fibers of 50 J.Lm and of 7 J.Lm for an A Vnodal cell, the ratio of conduction velocities, if these were only determined by cell diameter, would be 2.7. The actual ratio [2][3][4] mis for Purkinje fibers, 5 cm I s for A V node (58)] is much larger: 40 to 80.…”
Section: A Fiber Diametermentioning
confidence: 99%
“…There are only a few studies in which extracellular electrodes were used to record directly from the AV node (4,5,47,150,161,170,187). The interpretation of most extracellular waveforms recorded from the nodal area is very difficult.…”
Section: B Pattern Of E Xcitation Ofthe a V Nodementioning
confidence: 99%
“…As it has been reported that the refractory period of the intraventricular specialized conduction system is maximal at a level between the bundle of His and the ventricular myocardium, 12 it is obvious that time intervals recorded at the atrial and ventricular surfaces may not provide an accurate estimate of the time course of impulse propagation within the node. Accordingly, the present study was undertaken, utilizing a modification of the open heart preparation described by Alanis et al, 13 in order to appraise as closely as possible the role of the A-V node itself in the reciprocal propagation of impulses. Driving and premature stimuli, applied directly to the bundle of His, permitted the earliest possible premature penetration of the node; records of responses at the atrial margin of the node and at the His bundle defined the time attributable to intranodal transit.…”
mentioning
confidence: 99%